Dampak Keterlambatan Penyampaian Laporan Keuangan Terhadap Kinerja Keuangan Perusahaan Publik - Sutrisno, Tri (CV. Rayyan Dwi Bharata, 2025)
The main objective of this study is to analyze timelines of financial statement reporting and financial performance in Indonesian Stock Exchange (IDX). Samples in this study are IDX public companies listed in 1999-2005. The research questions are tested by running ANOVA to analyze whether any differences in timelines of financial statement reporting and financial performance between years and between size and also independent t test to analyze whether any differences in timelines of financial statement and financial performance between industry. Timelines (KW) proxied by dummy variable, 1 if companies published financial reporting before 120 days after December 31 and 0 otherwise. Financial performance proxied by Sales, Asset, Earning After Tax (EAT), Return on Investment (ROI), Return on Equity (ROE), and Sales Growth. The results of between year comparisons show that there are differences (increasing) between years for EAT, ROI and KW. These suggest that firm performance and timelines of financial statement reporting are increasing over time. The results of between size comparisons show that there are differences between size for EAT, Sales and KW. The bigger the size, the higher the financial performance and the timelines. The results of between industry comparisons show that there are differences for Asset and EAT. Base on these variables, financial performance in service industry higher than manufacture industry.